The Relationship Between The Level Of Defects And House-Buyers’ Satisfaction In Build-Then-Sell (BTS) Housing Delivery System - Fauzi, Siti Nur Fazillah Mohd (2011)
Build-Then-Sell (BTS) is a new system implemented in Malaysia after a number of complaints have been received from buyers in the Sell-Then-Build (STB) system. When the government announced the implementation of BTS in 2007, proponents of BTS have asserted that the new system will provide low defects‟ level. Their argument however was not supported by any empirical data. Hence, this study is conducted to measure the housing defects that can be found in BTS houses. The objectives of this study are manifold. First, it evaluates the housing defects in BTS houses. Secondly, it identifies the possible causes of those defects.